FRI0264 Cardiac Manifestations of Granulomatosis with Polyangiitis at Diagnostic. (9th June 2015) - Pugnet, G.; Puéchal, X.; Fillatre, P.; Terrier, B.; Decaux, O.; Guillevin, L.
Abstract : Background: Granulomatosis with polyangiitis (GPA, Wegener's granulomatosis) is an antineutrophil cytoplasm antibody (ANCA)–associated small-vessel vasculitis of unknown etiology, which is characterized by ear, nose, and throat (ENT); lung; and kidney involvement. Cardiac manifestations are generally considered rare in GPA patients, but they may be life-threatening. Objectives: The aim of this study was to determine the frequencies and types of cardiac manifestations in patients with granulomatosis with polyangiitis (Wegener's, GPA) at diagnosis. Methods: This retrospective analysis was conducted on the cardiac manifestations of GPA patients entered into the French Vasculitis Study Group database between July 1955 and September 2014. Results: Among the 671 identified patients, 39 (5.8%) had cardiac manifestations at diagnosis. Mean age at diagnosis was 51.1±20.1 years, with no remarkable sex predominance (male/female sex ratio, 1.4) and the median time from symptom onset to diagnosis was 2 months. The most frequent extracardiac manifestations at diagnosis were ENT (30, (77%)), pulmonary (29, (76.3%)) and renal (28, (71.8)) manifestations. The 3 most common recorded cardiac manifestations were pericarditis (16, (41%)), myocarditis (11, (28.2%)), and coronary vasculitis (5, (12.8%)). Aortic valvulopathy (4, (10.3%)) and arrhythmias (4, (10.3%)) were also common feature. Mean BVAS at diagnosis was 21.9±9.6. 25 (64.1%) GPA patients were PR3-ANCA positive. Median serum creatinine and CRP were 147 μmol/L (IQR: 82.5-283.5) and 112 mg/l (IQR: 14-202) respectively. Median follow-up was 37 months (IQR: 18-86). 15 (38.5%) experienced at least one relapse. 7 cardiac relapse occurred in 4 GPA patients, mostly pericarditis (5/7). 13 (33.3%) GPA patients died during follow-up. Conclusions: Cardiac manifestations at diagnosis were rare in GPA. They occurred in patients with a severe onset of the disease and close treatment and monitoring is critical. Disclosure of Interest: None declared